IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING (TBLT) ENGLISH CLASS FOR SECONDARY SCHOOL STUDENTS: A STUDY AT MADRASAH ALIYAH RADHIATUL ADAWIYAH MAKASSAR - Armansyah; Sukardi Weda; Chairil Anwar Korompot (International Journal of Business English and Communication, 2024)
This research has three objectives, they are to explore teacher’s perception, to investigate the implementation, and to investigate challenges of Task-Based Language Teaching (TBLT) in teaching basic speaking skills to secondary school students at Radiatul Adawiyah Foundation. By utilizing Descriptive Qualitative method, the research involved one English teacher as the research subject, with the data collected through interviews and observations. The results of the research indicate that the teacher views TBLT positively, recognizing it as an effective method that emphasizes practical language use. The teacher employs various interactive tools and methods, such as quizzes and the Alef platform, to engage students and enhance their language skills. However, the implementation of TBLT faces challenges as well, including students’ limited English proficiency, behavioral issues, and inconsistent attendance of students. These factors hinder the full potential of TBLT in improving students’ speaking skills. Despite these challenges, the teacher remains committed to TBLT, continuously adapting her methods to meet the diverse needs of her students.